MOTIVASI PENGUNJUNG KE KOTA WISATA BUKITTINGGI SUMATERA BARAT - Maihendro Dwisaputra; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The research was to known the motivation of tourist visiting the Tour of City of Bukittinggi of Province West Sumatera. The study aims to: (1) to know the motivations of tourists to Tour of City of Bukittinggi of Province West Sumatera. (2) to find out the most dominant motivation in tourists visiting the Tour of City of Bukittinggi of Province West Sumatera. This research uses descriptive quantitative method to describe the problems in a visit travellers. The sample used in this study is 100 people.Based on the results of the research that has been done, retrieved the motivation of tourists visit to the Tour of City of Bukittinggi of Province West Sumatera is influenced by a variety of motivation, such as physical motivation, fantasy motivation, and cultural motivation.While the most dominant motivation in the tourists visit to the Tour of City of Bukittinggi of Province West Sumatera is physical relaxation in the form of motivation, comfort, to culinary and shopping, and relax.Keywords: Motivation, Motivation of Travellers, Tour of City